INTERPRETATION OF CULTURAL REALITIES IN LITERARY TRANSLATION IN ENGLISH AND UZBEK - Abdullayeva Lolaxon Sobirjonovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Literary translation is not merely a linguistic process but also a cultural act that involves the interpretation and transfer of culturally marked elements from one language into another. Cultural realities such as national traditions, customs, historical references, and culture-specific concepts often pose significant challenges for translators. This article examines the ways cultural realities are interpreted and rendered in literary translation between English and Uzbek. The study analyzes common translation strategies, including domestication, foreignization, descriptive translation, and cultural substitution. Particular attention is paid to the balance between preserving national identity and ensuring comprehensibility for the target audience. The findings demonstrate that successful literary translation requires not only linguistic competence but also deep cultural awareness and interpretative skills.